State of The Art Review of Graduate Teacher Education Researches: Relevance to The National Research Priorities of National Higher Education Research Agenda-II - Vannessa D. Umali (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2020)
The state of the art review assesses the graduate research outputs in education produced by graduate teacher education students in selected public and private schools in the National Capital Region, Philippines during the School Year 2007-2016 based on national research priorities of National Higher Education Research Agenda-II. To provide a means of evaluating existing programs and to validate the result of the state of the art review of graduate education outputs – an expert validation was made among the Research and Development Directors from three (3) institutions of Polytechnic University of the Philippines (PUP), Eulogio